Directions in the utilization of crops for bio-energy in Malaysia in response to climate change. - Saleh, Ghizan; Rajanaidu, N. (International Society for Southeast Asian Agricultural Sciences, 2011)
Climate change has prompted countries to intensify efforts to utilize crops for renewable bioenergy, where Malaysia is not an exception. The government's seriousness in embarking on production and use of this alternative energy is seen from the establishment of the new Ministry of Energy, Green Technology and Water in April 2009, specifically devoted to focus on efforts to enhance development of bioenergy from alternative sources, and subsequently the launching of the National Green Technology Policy in July 2009. The National Biofuel Policy was formulated in March 2006 which envisages research and development, production, use and export of biofuel to ensure a cleaner environment, reduce reliance on fossil fuels, and to enhance and stabilize the price of palm oil. Being the most efficient oil crop, oil palm is by far the most highly utilized crop for biofuel in Malaysia, although some basic work are also currently being conducted on jatropha, cassava, sago palm and nipah palm. Though the development of indigenous technologies developed by the Malaysian Palm Oil Board, a desirable level of success has been achieved in production, utilization and export of biofuel from palm oil. Advancements have been made in the production of bio-diesel from palm oil, energy for burning and production of bio-ethanol using oil palm biomass from the mills, and methane trapping from palm oil mill effluent (POME) for industrial use. An even more sustainable approach is the utilization of the total oil palm biomass milling by-product for bioenergy. Research and development on the use of jatropha, a newly introduced crop, as a bioenergy crop is still at its infant stage. Although this crop has the ability to thrive well on marginal soils, research efforts need to be intensified on breeding for suitable varieties, pest and disease control, cultural practices and mechanization, particularly for the harvesting operations. The bioenergy industry in Malaysia faces challenges, which include competition in the price offered by biofuel from other oil plant sources, quality of biofuel produced and sustainability requirements imposed. This requires even more intensive research and development efforts, including those towards genetic improvement and development of new varieties to meet these specific needs.